Miskonsepsi dan Mispersepsi dalam Komunikasi di Sektor Publik: Dinamika Penyusunan Peraturan Daerah di Kabupaten Tasikmalaya: English - Laksana, Satya (Pahlawan 12 Press, 2020)
Misconceptions and misperceptions that occur in the public sector on a legal object is a phenomenon that can magnify the difficulty of implementing the regulation. This paper elaborates on misperceptions and misconceptions in public communication within the case study in the process of drafting the Regional Regulations (Perda) on the Protection of Sustainable Agricultural Land (LP2B) in Tasikmalaya District, West Java Province. By using descriptive methods this paper describes the dynamics of communication among stakeholders which are fulfilled with discourse, controversy, and ego-sectoral regarding the protection of LP2B in the period 2014-2019. Furthermore, this paper synthesizes the writer's own conceptions and arguments to correct the misperceptions and misconceptions based on academic references and relevant statutory arguments. The importance of this paper is for problem mapping and problem-solving of the complexity of LP2B protection in order to minimize discourse in public communication regarding LP2B. Policy implications are discussed.